Tren dan mode perkembangan Hijab di Indonesia - Salamah, Ika Hilmiatus; Tsabita, Fahmia Nuha; Balqis, Ummu Lathifah; Afifah, Nisrina Nur (Maliki Interdisciplinary Journal, 2023)
Abstract Hijab entered Indonesia in the 17th century marked by the presence of the queen of the Islamic kingdom in Aceh who used the headscarf as a dress at that time. Then over time, the hijab began to develop in Indonesia with various modes. Especially in recent years, the hijab has begun to develop with fashionable and modern trends. This article was written to examine the trend of hijab fashion which has been popular among the public for several years. This study uses a qualitative descriptive method with triangulation data collection techniques. The data source for this research is the verses of the Qur'an, the results of the survey are in the form of questionnaires to 50 respondents with the criteria of a Muslim student who wears a hijab, interpretations of scholars, scientific articles, and theses. This article describes the history of the hijab in Indonesia, including the trends and fashions of the Indonesian hijab from year to year, as well as the modern hijab phenomenon today which is much loved by the public, especially female students, and is also strengthened by several views of scholars from both a classical and contemporary perspective.